2020
DOI: 10.1016/j.neurad.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging findings in COVID-19: What do we know so far?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The pathophysiology of the hypercoagulable state in SARS-CoV-2 infection is multifactorial: it involves (i) an increase in acute-phase reactants (cytokine storm), (ii) endothelial damage sustained due to SARS-CoV-2, and (iii) diffuse microvascular injury with resulting thrombosis [ 6 ]. These findings are supported in a study by Md Noh [ 7 ], who found that patients with COVID-19 show prolonged prothrombin time, as well as increased D-dimer levels and low-normal platelet counts. While thromboembolic complications are relatively uncommon in COVID-19, it is important to keep them in mind because of their potential severity and the diversity of clinical presentations.…”
Section: Discussionsupporting
confidence: 68%
“…The pathophysiology of the hypercoagulable state in SARS-CoV-2 infection is multifactorial: it involves (i) an increase in acute-phase reactants (cytokine storm), (ii) endothelial damage sustained due to SARS-CoV-2, and (iii) diffuse microvascular injury with resulting thrombosis [ 6 ]. These findings are supported in a study by Md Noh [ 7 ], who found that patients with COVID-19 show prolonged prothrombin time, as well as increased D-dimer levels and low-normal platelet counts. While thromboembolic complications are relatively uncommon in COVID-19, it is important to keep them in mind because of their potential severity and the diversity of clinical presentations.…”
Section: Discussionsupporting
confidence: 68%
“…The COVID-19 is caused by the SARS-CoV-2. This coronavirus activates inflammatory and thrombotic pathways by binding the angiotensin-converting enzyme 2 receptors of endothelial cells, leading to an endotheliitis and a diffuse procoagulant state [7]. Our case suggests that the cerebral venous system can also be affected by this pathologic process.…”
mentioning
confidence: 74%
“…This is however, to our knowledge, the first description of a case with an associated cortical CVT. Other brain imaging abnormalities (arterial stroke or images compatible with acute disseminated encephalomyelitis) have been described [6]. The COVID-19 is caused by the SARS-CoV-2.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Coronavirus disease 2019 (COVID-19) is an acute infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is primarily characterized by pulmonary inflammatory lesions. It can also cause damage to the digestive system [ 1 3 ], nervous system [ 4 , 5 ], urinary system [ 6 ] and other systemic organs, with corresponding clinical symptoms. COVID-19 was identified as the health emergency of national concern by World Health Organization on 30 January, 2020 since its initial detection in December 2019 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%